The Pleasure of Art. Issue 1 (2nd January 2017) - Matthen, Mohan
ABSTRACT: This paper presents a new account of the pleasure we take in art. It distinguishes first between two types of pleasure. Relief or r-pleasure is transient and marks the end of a state that is difficult to maintain. Facilitation or f-pleasure accompanies an activity and lasts as long as the activity does. It motivates this activity and optimizes it by activating a suite of preparations and modes of acting specific to the activity. Aesthetic pleasure is a distinct form of f-pleasure. It arises from mental engagement with an object, and motivates and optimizes such engagement by activating a nexus specific to it. Aesthetic pleasure acts in two ways. In the short run, when we are in contact with a particular artefact, it keeps aesthetic engagement running smoothly. Over longer periods, it plays a critical role in shaping how we engage with objects to get this kind of pleasure from them. This account is yoked to a broadly functional understanding of art : it is not the nature of the object that makes it art, but the nature of the response that it is designed to elicit. The view does not, however, rest on individual psychology alone, as some other functional accounts do. Crucially, it is argued that shared cultural context is a key determinant of the pleasure we derive from aesthetic artefacts. The pleasure of art is always communal and communicative.